Business ethics and corporate image - Mínguez Arranz, Norberto (Área Abierta. Revista de comunicación audiovisual y publicitaria, 2002)
For a long time business and ethics were considered to be opposite concepts. The old saying “business is business” described a situation in which being ethical meant losing money. Ethics was understood as something that couldn´t be afforded, a luxurious element that had a mainly cosmetic use. Today business ethics is part of corporate life and we cannot understand corporate management without the concept of business ethics, a concept that also plays an important role in the construction of a good corporate image.